(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: PAX8 is a nuclear transcription factor with limited expression in normal and neoplastic tissues, it has the potential to induce tumorigenesis and is expressed in a tissue during neoplastic transformation. PAX8 is a useful marker to distinguish gynecologic cancers from non-gynecologic malignancies. Objective: To assess the immunohistochemichal expression of PAX8 in ovarian surface epithelial tumors. Methods: This study included a total of 100 ovarian tissue paraffin blocks, 70 tissue paraffin blocks of ovarian tumors obtained from patients who underwent total abdominal hysterectomy and bilateral salpingo-oophorectomy and 30 tissue paraffin blocks were the control group included normal ovarian tissue and fallopian tubes tissue. From each paraffin block, 2 sections were taken, one was stained with the routine hematoxylin and eosin stain and the other section was stained immunohistochemically for PAX8. Results: PAX8 showed a high significant difference in its immunohistochemical expression between the control group and the case group with the highest expression in malignant ovarian surface epithelial tumors (P < 0.001). Also, PAX8 showed a highly significance in the expression of PAX8 in relation to histopathological types (P < 0.001) except for the mucinous tumors, which showed statistically non-significance (P = 0.641), also, a highly significant relation with the increment of tumor grade (r = 0.769, P < 0.001). PAX8 showed a non-significant relation with increase of the age (r = 0.147, P= 0.225), with tumor stage (r = 0.433, P = 0.057), with the presence of ascites (P = 0.446). Conclusion: The highly significant differences in the immunohistochemical expression of PAX8 in the ovarian surface epithelial tumors tissues compared to the control groups reflect its important role in ovarian tumorigenesis. Besides PAX8 can be used as an important marker for discriminating ovarian non-mucinous from mucinous tumors. Also, there is a possible role of PAX8 in the development and differentiation of ovarian malignant surface epithelial tumor. Keywords: Ovarian surface epithelial tumors, ovarian carcinoma, transcription factor, paired box antigen, PAX8, immunohistochemistry Citation: Al-Shami SA, Qasim BJ, Hassan AM. Immunohistochemical expressions of PAX8 in ovarian surface epithelial tumors. Iraqi JMS. 2018; 16(3): 298-307. doi: 10.22578/IJMS.16.3.9